Non-coding RNAs fine-tune the balance between plant growth and abiotic stress tolerance - Zhang, Yingying; Zhou, Ye; Zhu, Weimin; Liu, Junzhong; Cheng, Fang (Frontiers in Plant Science, 2022)
To survive in adverse environmental conditions, plants have evolved sophisticated genetic and epigenetic regulatory mechanisms to balance their growth and abiotic stress tolerance. An increasing number of non-coding RNAs (ncRNAs), including small RNAs (sRNAs) and long non-coding RNAs (lncRNAs) have been identified as essential regulators which enable plants to coordinate multiple aspects of growth and responses to environmental stresses through modulating the expression of target genes at both the transcriptional and posttranscriptional levels. In this review, we summarize recent advances in understanding ncRNAs-mediated prioritization towards plant growth or tolerance to abiotic stresses, especially to cold, heat, drought and salt stresses. We highlight the diverse roles of evolutionally conserved microRNAs (miRNAs) and small interfering RNAs (siRNAs), and the underlying phytohormone-based signaling crosstalk in regulating the balance between plant growth and abiotic stress tolerance. We also review current discoveries regarding the potential roles of ncRNAs in stress memory in plants, which offer their descendants the potential for better fitness. Future ncRNAs-based breeding strategies are proposed to optimize the balance between growth and stress tolerance to maximize crop yield under the changing climate.